‘Wisdom is a gift given to the Wise’: Florence Farr (1860–1917): New Woman, Actress and Pagan Priestess - Muriel Pécastaing-Boissière (Cahiers Victoriens et Edouardiens)
According to Caroline Wise, who wrote her Oxford Dictionary of National Biographies entry, in Florence Farr: ‘[t]he mystical, the philosophical and the political wove a seamless whole in an active, questing and pioneering life’. Nevertheless, Farr has long been studied almost exclusively as George Bernard Shaw’s or William Butler Yeats’s so-called ‘Muse’. Admittedly, Shaw and Yeats wrote leading parts for her, but it was she who commissioned and staged some of their very first plays. Furthermore, Shaw strongly disapproved of Farr’s occult studies as a leading member of the Golden Dawn. Yeats, for his part, also was a member of the Golden Dawn, and he collaborated with Farr for over twenty years. Together, they explored the ‘music of speech’, that they considered as the lost art of ‘cantilating’ poetry. They made no secret of the pagan and mystic roots of their art. To Yeats, Florence Farr was less an actress and a composer than a priestess and a bard. Farr’s method was inspired by her Golden Dawn rituals, when she already combined poetry and contrapuntal music, according to the theory of harmonic convergence. Nevertheless, the central relevance to Farr’s and Yeats’s artistic endeavours of her occult work and study has constantly been played down. So I chose to put Florence Farr back onto centre stage and explore her influential role in the pagan revival of the late Victorian and Edwardian era from her own perspective, i.e. that of a New Woman and an artist. My aim is to demonstrate how Farr’s feminism, artistic creativity and spiritual quest constantly enriched one another and left a deep impression on those who met her.